Clinical and Dermoscopic Evaluation of Melasma: A Study of Patterns, Severity, and Associated Risk Factors - Mohammad, Ali Jafar; Sahib, Nadia H.; Fakhry, Fatin Ahmed; Mohammed, Mohammed Abbas; Sameir, Mohammed (American Journal of Biomedicine and Pharmacy, 2026)
Melasma is a common acquired hyperpigmentary disorder characterised by symmetrical brown macules and patches affecting mainly sun-exposed facial areas. It predominantly occurs in women of reproductive age and is strongly associated with ultraviolet radiation, hormonal influences, pregnancy, oral contraceptive use, and genetic predisposition. Dermoscopy has emerged as an important non-invasive diagnostic tool for evaluating pigment depth, vascular changes, and prognostic features. This study aimed to evaluate the clinical and dermoscopic characteristics of melasma, assess disease severity using the Melasma Area and Severity Index (MASI), and determine the association between dermoscopic findings and major clinical risk factors. This study included 80 patients with clinically diagnosed facial melasma attending the dermatology outpatient clinic. Demographic and clinical data were collected, including age, sex, skin phototype, family history, oral contraceptive use, topical steroid use, sun exposure, and pregnancy-related melasma. Clinical classification was based on facial distribution patterns. Dermoscopic examination was performed using a handheld dermoscope with ×10 magnification. MASI scoring was used to assess severity. The mean age was 34.5 ± 5.2 years, and females represented 95.0% of cases. Malar melasma was the predominant clinical pattern (72.5%). Brown background pigmentation (90.0%), irregular pigment network (87.5%), and brown globules and dots (97.5%) were the most frequent dermoscopic findings. Telangiectasia was present in 77.5% of patients. Sun exposure showed a significant association with telangiectasia (OR = 4.67; 95% CI: 1.28–16.99; p = 0.023). Dermoscopy provides valuable diagnostic and prognostic information in melasma and supports individualised management strategies.